KARAKTERISTIK PENDERITA DIABETES MELLITUS TIPE 2 DENGAN KOMPLIKASI YANG DIRAWAT INAP DI RUMAH SAKIT UMUM DAERAH (RSUD) DR. R. M. DJOELHAM BINJAI TAHUN 2014 – 2015 - mangara sitohang; Hiswani .; Mhd Makmur Sinaga (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Abstract Diabetes Mellitus (DM) is one of health’s problems in the world. According to World Health Organization (2003), people in the world with diabetes 5,1%. Based on data from Riset Kesehatan Dasar (2007), the prevalence of diabetes was 5,7% in Indonesia. In North Sumatra, the prevalence of DM was 1,2% in 2008. The purpose of this study is to know the characteristics of patients of type 2 DM with complications who were hospitalized in RSUD Dr. R. M. Djoelham Binjai in 2014 – 2015. This research is descriptive with case series design. The population and the samples were all the patiens of type 2 diabetes with complications, 148 cases. The data was collected by using secondary data and analyzed with Chi-Square and Kruskal Wallis. The result showed the proportion of patiens with complications of type 2 DM was highest in the age group >40 tahun (85,1%), female (55,4%), Javanese (35,8%), Moslem (68,2%), Senior High School (55,4%), worker (53,4%), hypertension (52,7%), chronic complication (41,9%), oral hypoglycemic medicine (44,6%), not self-cost (77,7%), average length of stay (4,89 days), becoming outpatient (89,9%). The statictical test resulted, there was no difference of age based on sex (p=0,580), age based on category of complication (p=0,427), sex based on category of complication (p=0,060), job based on category of complication (p=0,625), category of complication based on medicine (p=0,573), category of complication based on condition by going home (p=0,909). It’s suggested for RSUD Dr. R. M. Djoelham Binjai for checking blood glucose regularly to the patients for monitoring amount of glychemic and the obedience of patients in controlling theirs blood glucose. The patients of type 2 DM with complications sholud control blood glucose regularly, perform the recommended diet, regular exercise, adopt healthy lifestyle, and consume medicine regularly so that blood glucose can be controlled for preventing more serious complications. Keywords : Characteristics, Type 2 Diabetes Mellitus with Complications